Transcriptome of the plant virus vector Graminella nigrifrons, and the molecular interactions of maize fine streak rhabdovirus transmission. - Yuting Chen; Bryan J Cassone; Xiaodong Bai; Margaret G Redinbaugh; Andrew P Michel (PLoS ONE, 2012)
BACKGROUND: Leafhoppers (HEmiptera: Cicadellidae) are plant-phloem feeders that are known for their ability to vector plant pathogens. The black-faced leafhopper (Graminella nigrifrons) has been identified as the only known vector for the Maize fine streak virus (MFSV), an emerging plant pathogen in the Rhabdoviridae. Within G. nigrifrons populations, individuals can be experimentally separated into three classes based on their capacity for viral transmission: transmitters, acquirers and non-acquirers. Understanding the molecular interactions between vector and virus can reveal important insights in virus immune defense and vector transmission. RESULTS: RNA sequencing (RNA-Seq) was performed to characterize the transcriptome of G. nigrifrons. A total of 38,240 ESTs of a minimum 100 bp were generated from two separate cDNA libraries consisting of virus transmitters and acquirers. More than 60% of known D. melanogaster, A. gambiae, T. castaneum immune response genes mapped to our G. nigrifrons EST database. Real time quantitative PCR (RT-qPCR) showed significant down-regulation of three genes for peptidoglycan recognition proteins (PGRP - SB1, SD, and LC) in G. nigrifrons transmitters versus control leafhoppers. CONCLUSIONS: Our study is the first to characterize the transcriptome of a leafhopper vector species. Significant sequence similarity in immune defense genes existed between G. nigrifrons and other well characterized insects. The down-regulation of PGRPs in MFSV transmitters suggested a possible role in rhabdovirus transmission. The results provide a framework for future studies aimed at elucidating the molecular mechanisms of plant virus vector competence.